Perinatal hormones favor CC17 group B Streptococcus intestinal translocation through M cells and hypervirulence in neonates - Constantin Hays; Gérald Touak; Abdelouhab Bouaboud; Agnès Fouet; Julie Guignot; Claire Poyart; Asmaa Tazi (eLife, 2019)
Group B Streptococcus (GBS) is the leading cause of invasive bacterial neonatal infections. Late-onset diseases (LOD) occur between 7 and 89 days of life and are largely due to the CC17 GBS hypervirulent clone. We studied the impact of estradiol (E2) and progesterone (P4), which impregnate the fetus during pregnancy, on GBS neonatal infection in cellular and mouse models of hormonal exposure corresponding to concentrations found at birth (E2-P4 C0) and over 7 days old (E2-P4 C7). Using representative GBS isolates, we show that E2-P4 C7 concentrations specifically favor CC17 GBS meningitis following mice oral infection. CC17 GBS crosses the intestinal barrier through M cells. This process mediated by the CC17-specific surface protein Srr2 is enhanced by E2-P4 C7 concentrations which promote M cell differentiation and CC17 GBS invasiveness. Our findings provide an explanation for CC17 GBS responsibility in LOD in link with neonatal gastrointestinal tract maturation and hormonal imprint.